Evaluation Of Local Revenue As An Instrument Of Regional Fiscal Strengthening In The Maluku Islands: Elasticity And Effectiveness Approach - Sangadji, Maryam; Siregar, Indra Saputra; Oktantiasari, Aisyah; Assel, Muhammad Ridhwan (e-Journal Ekonomi Bisnis dan Akuntansi, 2025)
This study aims to 1) Analyze the level of elasticity of local own-source revenue (PAD) to gross regional domestic product (GRDP), 2) Evaluate the level of effectiveness of PAD target achievement and 3) Assess the role of PAD in strengthening regional fiscal capacity. Through the elasticity and effectiveness approaches, the results show 1) the elasticity of PAD to GRDP in Maluku Province shows a moderate average value (1.13), but there are significant disparities between regions. Ambon City and MBD were highly volatile, while SBT recorded negative elasticity; 2)  The effectiveness of PAD in Maluku Province and Ambon City was high and stable, while Central Maluku and Southwest Maluku showed low and fluctuating effectiveness. East Seram Regency recorded very high but inconsistent effectiveness, driven by incidental revenues, which reflects the lack of a strong regional fiscal capacity structure. The degree of fiscal decentralization in Maluku Province and the four districts/municipalities is still classified as low to very low, with the dominant pattern of fiscal relations being “instructive” and “consultative”. This reflects limited regional fiscal capacity and high dependence on central transfers, especially in district areas such as East Seram and Central Maluku.